2018
DOI: 10.1177/0300060518762986
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and radiologic characteristics of isthmus parameters in guiding pedicle screw placement

Abstract: ObjectiveTo study the clinical application of lumbar isthmus parameters in guiding pedicle screw placement.MethodsLumbar isthmus parameters were measured in normal lumbar x-rays and cadaveric specimens from a Chinese Han population. Distance between the medial pedicle border and lateral isthmus border was recorded as a ‘D’ value and was compared between X-rays and cadavers. Orthopaedic surgeons estimated different distances (2–6 mm) and angles (5–20°), and bias ratios between estimated and real values were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…As shown in our previous study (Table 1) 12 , the mean deviation degree of the angle (105.5%) determined by the orthopaedic clinician was significantly higher than the average deviation degree of distance (14.33%). These findings indicated that the accurate determination of distance was easier.…”
Section: Distance and Angle Assessmentsupporting
confidence: 57%
See 4 more Smart Citations
“…As shown in our previous study (Table 1) 12 , the mean deviation degree of the angle (105.5%) determined by the orthopaedic clinician was significantly higher than the average deviation degree of distance (14.33%). These findings indicated that the accurate determination of distance was easier.…”
Section: Distance and Angle Assessmentsupporting
confidence: 57%
“…Isthmus parameters, including D1 12 , D2, and D3, were introduced into the process of screw placement. The D2 value was measured as the vertical distance between the line connecting the vertexes of the isthmus and the inferior border of the transverse process.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations